Application of a didactic sequence: the collaborative scientific doing for the teaching of chemistry in basic education - Salome Ramos Medeiros, Maria (Seven Editora, 2023)
This article is the result of a research that focused on the study of scientific doing with collaborative proposals and as a field of study, "Chemistry and Cooking". In this journey, we sought to boost the teaching-learning process of Chemistry, establishing the School as an ideal space for stimulating scientific research and building a fair, democratic and inclusive society, based on daily practical activities. The research was divided into the following stages: bibliographic review for the formation of a database on the subject under study, followed by the application of a didactic sequence with collaborative proposals for second and third year high school students of the Technical course in Agroecology of a school in the state school, in a small town in the interior of Bahia, in 2021. After the application of the didactic sequence, in possession of the data, the analysis was made, finally presenting the results of the research. It is noteworthy that, during an asynchronous period, scientific research had the help of some digital tools, such as online laboratories and their potentialities, for the beginning of practical activities in the discipline of Chemistry in high school. DOI: https://doi.org/10.56238/tfisdwv1-088